Control of Protonated Schiff Base Excited State Decay within Visual Protein Mimics: A Unified Model for Retinal Chromophores. Issue 66 (28th October 2021) - Demoulin, Baptiste; Maiuri, Margherita; Berbasova, Tetyana; Geiger, James H.; Borhan, Babak; Garavelli, Marco; Cerullo, Giulio; Rivalta, Ivan
Abstract: Artificial biomimetic chromophore‐protein complexes inspired by natural visual pigments can feature color tunability across the full visible spectrum. However, control of excited state dynamics of the retinal chromophore, which is of paramount importance for technological applications, is lacking due to its complex and subtle photophysics/photochemistry. Here, ultrafast transient absorption spectroscopy and quantum mechanics/molecular mechanics simulations are combined for the study of highly tunable rhodopsin mimics, as compared to retinal chromophores in solution. Conical intersections and transient fluorescent intermediates are identified with atomistic resolution, providing unambiguous assignment of their ultrafast excited state absorption features. The results point out that the electrostatic environment of the chromophore, modified by protein point mutations, affects its excited state properties allowing control of its photophysics with same power of chemical modifications of the chromophore. The complex nature of such fine control is a fundamental knowledge for the design of bio‐mimetic opto‐electronic and photonic devices. Abstract : A joint experimental‐computational study elucidates the photophysics of retinal Schiff bases embedded in artificial proteins capable of mimicking the color tunability of natural visual pigments as compared to solvated chromophores. Combining ultrafast transient absorption spectroscopy with quantum mechanics/molecular mechanics simulations allowed monitoring nonlinear optical signals of the chromophore, shedding light on the complexity beyond the fine control of its excited state lifetime.